MORPHOLOGICAL STUDY OF POECILIA RETICULATA (PETERS, 1860) - TIWARI, VISHAL; GAUR, K.K; RANI, RITA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
The present study aimed at to notice the morphology of Poecilia reticulata (Peters, 1860). Body size, colouration, presence of gonopodium in male and gravid spot in female fish were some of the morphological features studied during the investigation. These were promiscuous dimorphic features, thereby, facilitating their recognition and distinction formating.